2009
DOI: 10.1099/jmm.0.010231-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of espM and espT among enteropathogenic and enterohaemorrhagic Escherichia coli

Abstract: Enterohaemorrhagic Escherichia coli (EHEC) and enteropathogenic E. coli (EPEC) translocate dozens of type III secretion system effectors, including the WxxxE effectors Map, EspM and EspT that activate Rho GTPases. While map, which is carried on the LEE pathogenicity island, is absolutely conserved among EPEC and EHEC strains, the prevalence of espM and espT is not known. Here we report the results of a large screen aimed at determining the prevalence of espM and espT among clinical EPEC and EHEC isolates. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…S1), has shown that the gene is present in ca. 1.8% of the tested strains [21]. In order to investigate the role of EspT in cell invasion we selected to use the espT positive strains E110019 and C. rodentum ; the espT negative EPEC, strain JPN15 [38], was used as a control.…”
Section: Resultsmentioning
confidence: 99%
“…S1), has shown that the gene is present in ca. 1.8% of the tested strains [21]. In order to investigate the role of EspT in cell invasion we selected to use the espT positive strains E110019 and C. rodentum ; the espT negative EPEC, strain JPN15 [38], was used as a control.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, IpgB1 was described to drive Rac1 and Cdc42 activation (19). In addition, more recently identified family members such as EspM and EspT have been interpreted to activate rather than mimic RhoA and Rac1/Cdc42, respectively (20,21), which was recently verified in the case of EspM2 (22). The finding that the WXXXE protein SifA displays a fold similar to the bacterial GEF SopE (15,23) provided the first structural evidence for WXXXE proteins acting as GEFs.…”
mentioning
confidence: 87%
“…In addition, the Nle effectors Ibe (invasion of endothelial cells) and EspT have been originally described and characterized in aEPEC strains 102, 103. Ibe appears to regulate Tir phosphorylation and to enhance actin polymerization and pedestal formation, 103 while EspT 104 modulates actin dynamics, leading to membrane ruffling and cell invasion, and induces macrophages to produce interleukins IL-8 and IL-1β and PGE2 102 …”
Section: Typical and Atypical Enteropathogenic E Colimentioning
confidence: 99%